Effectiveness of High-flow Nasal Cannula (HFNC) over Continuous Positive Airway Pressure (CPAP) as A Primary Mode of Respiratory Support in Children : A Review - Mamun, Mohammad Abdullah Al; Saha, Debosree; Hossain, M Monir (Dhaka Shishu (Children) Hospital Journal, 2026)
HFNC provides heated, humidified gas which minimizes metabolic cost and eliminate effects of cooling and drying. It optimizes oxygenation, meets inspiratory demand and decreases inspiratory and expiratory work of breathing also wash out of pharyngeal dead space and helps in CO2 removal. It’s use has been expanded to all causes of acute hypoxemic respiratory failure, especially in bronchiolitis, and in post-extubation respiratory failure as well, starting from Emergency Department, Pediatric Ward, Pediatric Intensive Care Unit (PICU), Neonatal Intensive Care Unit (NICU) and during transportation. It is well tolerated than CPAP, BiPAP and NIPPV. Continuous positive airway pressure (CPAP) is frequently used as the recommended treatment option for respiratory distress but it has some adverse events. In this review it is not about comparing HFNC with CPAP, because both comparisons are not of equal modalities, it is to understand what is the right place of HFNC therapy in children. DS (Child) H J 2024; 40(1): 51-55